The Effect of Work Environment and Motivation on Employee Performance at PT. Agro Sinergi Nusantara Aceh Barat - Al Mouliza; Damrus Damrus; Muzakir Muzakir; Nabila Hilmy Zhafira (PT. Intelek Cendikiawan Nusantara, 2026)
This study analyzes the challenges companies in Pekanbaru City face in attracting Generation Z talent amidst This study aims to determine the influence of work environment and work motivation on employee performance at PT. Agro Sinergi Nusantara West Aceh. The approach used in this study is a quantitative correlational approach to test the influence between variables. The population in this study were all employees of PT. Agro Sinergi Nusantara West Aceh, totaling 397 people. The sampling technique used the Slovin formula with an error rate of 10%, resulting in a sample of 80 respondents, selected using a simple random sampling technique. Data sources were obtained through the distribution of closed questionnaires with a Likert scale of 1–5. Data analysis was carried out using multiple linear regression through SPSS software version 27, with prior validity tests, reliability tests, and classical assumption tests. The results showed that partially the work environment variable (X1) had a positive and significant effect on employee performance (Y) with a t- count value of 8.658> t-table 1.990 and a sig. value of 0.000 <0.05. The work motivation variable (X2) also partially had a positive and significant effect on employee performance (Y), with a calculated t-value of 3.733 > t-table 1.990 and a sig. 0.000 < 0.05. Simultaneously, the work environment (X1) and work motivation (X2) variables significantly influenced employee performance (Y), with a calculated F-value of 70.403 > F-table 3.110 and a sig. 0.000 < 0.05. These findings indicate that a conducive work environment and positive work motivation play a significant role in improving employee performance at PT. Agro Sinergi Nusantara West Aceh. Based on these findings, the company is advised to improve the quality of work communication, strengthen social relationships between employees, and increase employee reliability in carrying out tasks to encourage sustainable performance improvement.